Case report: A preterm infant with rubinstein-taybi syndrome and Marmorata telangiectatica harboring a frameshift mutation in the CREBBP gene - Yang, Yang; Xiao, Jing; Ye, Yuanyuan; Xiang, Jianwen; Wang, Zhu; Chen, Jia (Frontiers in Pediatrics, 2023)
Backgroud Rubinstein-Taybi syndrome (RTS) is an autosomal inherited disease,associated with de novo variants in the epigenetics-associated gene, CREBBP.It is characterized by mental and growth retardation,skeletal abnormalities,and dysmorphic facial features.Cutis marmorata telangiectatica congenita (CMTC) is a benign vascular anomaly. Diagnosis of CMTC is made on the basis of clinical features. Case presentation Herein, we report on a preterm infant with CMTC and polydactyly who had a frameshift mutation leading to a premature stop codon in the CREBBP. The mutation, c.5837dupC, reported in this paper enlarges on the known molecular spectrum of disease-causing CREBBP gene. Conclusions This child suffered from RTS and CMTC.Other cases have reported that the mutation c.5837dupC of CREBBP got other skin lesions. It is inferred that the two diseases may have a common pathogenesis. There are few cases of polydactyly and syndactyly in the patients of RTS among different races, but the findings in other provinces of China are different. Therefore, the clinical phenotype of RTS may be different among different races.But both all more studies are needed to confirm it.